Analisis Komunikasi Krisis Public Relations PT. Hayati Pratama Mandiri Kota Padang Pada Kasus Patahnya Rangka Esaf (Enhanced Smart Architecture Frame) - Vazar Cahyanto; Dion Eriend (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study examines the crisis communication strategies implemented by the Public Relations department of PT. Hayati Pratama Mandiri in Padang City in response to the fractured Enhanced Smart Architecture Frame (ESAF) issue in Honda motorcycles. The study adopts the Situational Crisis Communication Theory (SCCT) proposed by Coombs, which emphasizes that public attributions toward a crisis influence an organization's reputation. This theory also highlights the importance of protecting the public and stakeholders rather than merely preserving the company's image. The findings reveal that PT. Hayati Pratama Mandiri employed a well-planned and transparent crisis communication strategy, utilizing adaptive and dynamic approaches to manage the situation. The company conducted a thorough investigation, provided 24-hour customer service, and enhanced frame protection against corrosion. Its open and responsive communication approach effectively mitigated negative impacts and restored brand perception among consumers. This research underscores that crisis management and communication are vital elements in Public Relations functions. With the right strategy, the company not only managed the crisis effectively but also reinforced its reputation as a responsible and quality-oriented entity. This study offers valuable insights into best practices in crisis communication that can be applied to similar challenges in the future.